Pengaruh Brand Credibility, Brand Love Dan Brand Commitment Terhadap Word Of Mouth (Wom) Pada Merek X - Chairy, Akiko dan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The purpose of this research was to determine the effect brand love, brand commitment and brand credibility X brand products to word of mouth (WOM). The type used in this research is descriptive method that is using method with fact finding through proper interpretation. Population in this research is people who use X brand products.  The method used in sampling is non-probability sampling method with purposive sampling technique which is a sampling technique by selecting sampling unit on the basis of certain criteria. The period of questionnaire taking starts in May-August 2017. The data obtained will be analyzed using Structural Equation Modeling (SEM)-AMOS. The result of this research indicates Brand Credibility and Brand Love have significant effect to Word Of Mouth on product brand X with Brand Commitment as intervening variable at significance 5%. In addition, Brand Commitment has a significant effect on Word Of Mouth. Advice that given to the Brand x is Company need to maximize to satisfy customer so that customer who used “X” brand products will talk to people through word of mouth